Sedentary Behaviour and Physical Activity of People with Stroke in Rehabilitation Hospitals - Anna Sjöholm; Monica Skarin; Leonid Churilov; Michael Nilsson; Julie Bernhardt; Thomas Lindén (Stroke Research and Treatment)
Background. Sedentary behaviour is associated with health risks, independent of physical activity. This study aimed to investigate patterns of sedentary behaviour and physical activity among stroke survivors in rehabilitation hospitals. Methods. Stroke survivors admitted to four Swedish hospital-based rehabilitation units were recruited ≥7 days since stroke onset and their activity was measured using behavioural mapping. Sedentary behaviour was defined as lying down or sitting supported. Results. 104 patients were observed (53% men). Participants spent an average of 74% (standard deviation, SD 21%) of the observed day in sedentary activities. Continuous sedentary bouts of ≥1 hour represented 44% (SD 32%) of the observed day. A higher proportion (30%, SD 7%) of participants were physically active between 9:00 AM and 12:30 PM, compared to the rest of the observed day (23%, SD 6%, P<0.0005). Patients had higher odds of being physically active in the hall (odds ratio, OR 1.7, P=0.001) than in the therapy area. Conclusions. The time stroke survivors spend in stroke rehabilitation units may not be used in the most efficient way to promote maximal recovery. Interventions to promote reduced sedentary time could help improve outcome and these should be tested in clinical trials.